The effect of Camellia sinensis tea on a decreased risk of anxiety for medical students at Universitas Lambung Mangkurat Indonesia - Mohammad Bakhriansyah; Sidnan Naufa Sulaiman; Rahmi Fauzia (Elsevier, 2022)
Background: Anxiety is a response for inability to overcome problems that commonly occurs in medical students, thus affecting their academic performances. The content of l-theanine in Camellia sinensis (C. sinensis) tea is able to cause a relaxing effect to reduce anxiety. Objectives: The purpose of this study was to determine the effect of Camellia sinensis (C. sinensis) tea consumption on anxiety level in medical students. Method: This was an analytic observational with cross-sectional approach within 332 undergraduate students at Medical Faculty ULM in December 2021. They were selected using simple random sampling technique. Data were collected online via Google form. A questionnaire and The Zung Self-rating Anxiety Scale were applied to figure out characteristics of respondents including tea consumption status, and to determine the anxiety status, respectively. Data were then analyzed using a multinomial logistic regression test. Results: This study demonstrated that consuming tea occasionally (≥1 glass per week) showed a lower risk of mild-moderate anxiety by 9% (adj. OR 0.91, 95%CI: 0.47-1.77) and of marked-severe anxiety by 46% (adj. OR 0.55, 95%CI: 0.12-2.43) compared to non-tea drinkers. Meanwhile, consuming 1 glass and 2-3 glasses of tea per day showed a 20% (adj. OR 0.80, 95%CI: 0.36-1.79) and a 54% (adj. OR 0.46, 95%CI: 0.15-1.37) lower risk of mild-moderate anxiety, respectively compared to non-tea drinkers. However, this association was not statistically significant (p>0.05). Conclusions: These results indicate that there is a tendency of a decreased risk of anxiety for the increased consumption of C. sinensis tea.